Early hydration characteristics and kinetics model of cement pastes containing internal curing materials with different absorption behaviors. (20th June 2023) - Zhang, Gengtong; Xia, Huiyun; Wang, Hao; Song, Lifang; Niu, Yanhui; Cao, Dongwei; Chen, Huaxin
Highlights: Early hydration kinetics model of IC materials with different absorption behavior was studied. Effect of IC materials on microstructure and hydration products of cement paste was investigated. The hydration degree and rate of cement can be promoted by increasing the dosage of composite microgel. Hydration characteristics are in good agreement with the hydration kinetic model. Abstract: Internal curing with superabsorbent polymer (SAP) has potential effect on the early deformation and hydration of cementitious material. However, there are few studies on the hydration kinetics and hydration characteristics of internal curing cementitious material. Here, the effects of microgel, composite microgel and commercial SAP with different dosage and absorption behaviors on the hydration characteristics of cement paste were studied by the hydration model proposed by Krstulović-Dabić and hydration heat. Results showed that the hydration reaction of paste containing internal curing materials increased as function of the dosage. When nano-silica(NS) incorporated into microgel, 24.5% and 5.6% increase in value of exothermic peak and cumulative heat were observed for paste. The hydration kinetic model showed that the composite microgel promoted the crystal growth and phase boundary reaction process, thus extending the transition point to the diffusion process. For commercial SAP with premature desorption behavior, the hydration rate of cement paste decreases and the appearance of conversion point at each process is delayed. Hydration characteristics are in good agreement with the kinetic model, suggesting that portlandite consumed by pozzolanic reaction promoted the development of hydration reaction and further refined the microstructure of paste.